Chimeric Visions: Posthuman Somaesthetics and Interspecies Communication in Contemporary Humanimal Body Art Performances - Kérchy, Anna (Hungarian Journal of English and American Studies, 2021)
Body art performances experiment in provocative, transgressive ways with the human body that becomes, simultaneously, an instrument, a medium, an agent, and an end product of artistic creation. They invite calculated corporeal reactions from audiences in a multitude of affectively, perceptually, and politically engaging ways. A brief overview is given of the evolution of body art from its roots in avant-garde performance arts to current trends of carnal art to shed light on the changing cultural-historical interpretation of human embodiment. It reveals how body art’s growing dissatisfaction with anthropocentrism entails an inevitable move toward humanimal poetics and politics. The shift of focal point from humanoid embodiment to interspecies relationalities and posthuman enworldedness marks a major paradigm shift of body art. Mapping the aesthetic manifestations, ethical stakes, and corporeal experience of this shift—that extends the notion of subjectivity beyond the human species—is the main aim of the essay. (AK)